Letteratura della crisi - Corrado, Sergio (Kritik. Rivista di letteratura e critica culturale, 2023)
In the crisis discourse, which is increasingly present in the media, the crisis (be it economic, military, climatic or pandemic) is a dramatic event, which happens in a condensed time and admits only opposing outcomes: “salvation” or “condemnation”. Instead, for literature it is a daily existential dimension, which lasts while waiting for the crisis to end. But what is the specificity of the literary codification of a crisis? Literature investigates lived time, dilates it, reworks it thanks to its metamorphic potential; it reconstructs individual and collective stories in a non-linear way that does not conform to mainstream culture, it changes the perception of the present by transforming it symbolically (like street art in the Athens of the recent economic crisis). By suspending the binary logic of technocratic and institutional languages, literature can offer an alternative phenomenology of the probable and the possible.